IMPLEMENTASI PENGALIHAN PAJAK BUMI BANGUNAN PERDESAAN DAN PERKOTAAN (PBB P2) SEBAGAI PAJAK DAERAH DALAM PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Amelia, Ratih; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Since Law Number 28 Year 2009 was regalized, all of relating Land and Building Tax (P&B Tax) Of Rural and Urban have been transfered to local goverments. The locals goverments are expected to explore the exsisting potential, as well as be able to increase the District Own Source Revenue (DOSR) especially those steamming from Land and Building (P&B Tax) Of Rural and Urban. But in fact, the collecting of Land and Building (P&B Tax) Of Rural and Urban in Bagan Sinembah Sub-District Rokan Hilir Regency has not run optimally yet. It can be proven by the result of recapitulation of acceptance has no reached the set target yet. Theoretical concept used is implementation in Van Meter and Van Horn who said that there was several variables that affected the performanced of the public policy implementation, such as : standard and policy objectives, resources, communication between organization, the characteristic of implementers, the condition of social economic and political, as well as implementers disposition. This research used qualitative method by using snowball as information and the data analys thecnique by using triangulation technique. Result of the research showed that The implementation Of Transfer Of Land and Building Tax (P&B Tax) Of Rural and Urban As The Regional Tax In Increasing District Own Source Revenue (DOSR) has not run optimally. This was due to the limited human resources and infrastructure, the lack of awareness taxpayer, and sanctions that did not run in the accordance with provisions, the data of taxpayer did not accomodated as well as people’s economic conditions in Bagan Sinembah-Sub-District Rokan Hilir Regency.Keywords : Land and Building Tax (P&B Tax) Of Rural and Urban, Implementation, District Source Own Revenue (DOSR)